2009
DOI: 10.31729/jnma.214
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Lump: A Diagnostic Dilemma

Abstract: Abdomen is a Pandora's Box. During our routine patient evaluation we come across different types of abdominal lumps out of which some are straight forward and diagnosed after routine clinical examinations and available investigations. At times these abdominal lumps present differently from their usual presentations and create confusions despite undergoing necessary investigations. The truth is explored only after opening the Pandora's Box. We present a case of 21 years old male who presented with history of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…The few data in dogs indicate higher prevalence in areas where livestock is slaughtered [149] , [152] . Since the 2000s, various case reports have been published on human hydatidosis [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] , [161] . Hospital register studies for CE cases have found low incidences [147] , [162] , [163] .…”
Section: Resultsmentioning
confidence: 99%
“…The few data in dogs indicate higher prevalence in areas where livestock is slaughtered [149] , [152] . Since the 2000s, various case reports have been published on human hydatidosis [153] , [154] , [155] , [156] , [157] , [158] , [159] , [160] , [161] . Hospital register studies for CE cases have found low incidences [147] , [162] , [163] .…”
Section: Resultsmentioning
confidence: 99%
“…9 An ultrasound-guided percutaneous nephrostomy tube should be placed in patients with fever or raised serum creatinine levels. 10 They can also be placed for providing rapid symptomatic relief. 6 An assessment of renal function should be done to determine further treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Bhandari and Shrestha (2019) found that internal control systems in cooperative societies in Nepal are generally weak and ineffective due to lack of proper training and resources. The study found that many cooperative societies in Nepal struggle with issues such as financial mismanagement, embezzlement, and lack of transparency.…”
Section: Empirical Evidences and Research Gapmentioning
confidence: 99%